DAAI TV dan Gereja : Kesadaran Bermedia dalam Terang Perdamaian Universal - Leidi Asterina Lontaan; Prisilia J. Pausther (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2021)
This paper aims to provide what contributions DAAI TV has given to peace efforts based on universal values, and to see how the church responds to television media, and whether the church has become a community that consistently runs and promotes peace in society. The research method used is a descriptive analysis of DAAI TV and also awareness of media in peace efforts. The results of the research obtained are from DAAI TV, the church needs to learn about the principle of peace based on universal love. The church needs to learn to be an open church, not judging anyone, but willing to embrace anyone. The church must be ready to 'break down' the walls or barriers that limit the scope of this love. The church opens its eyes to humanitarian issues that undermine various lines of human life, in which the church is present as a witness of peace.